Channel modulation by tyrosine phosphorylation in an identified leech neuron. - Aniksztejn, L (1997)
1. We have examined the effects of tyrosine phosphorylation on a spontaneously active cation channel that also participates in the modulation of pressure-sensitive (P) neurons in the leech. Cation channel activity in cell-attached or isolated, inside-out membrane patches from P cells in culture was monitored before and after treatments that altered the level of tyrosine phosphorylation. 2. In cell-attached recordings from intact P cells, bath application of genistein, an inhibitor of tyrosine kinases, resulted in a 6.6 +/- 2.6-fold increase in channel activity with no change in the mean open time or amplitude. Daidzein, an inactive form of genistein, was without effect. Addition of pervanadate, a membrane-permeant inhibitor of tyrosine phosphatases, had no effect on its own and blocked the effect of subsequent addition of genistein. 3. In inside-out P cell membrane patch recordings, exposure to a catalytically active fragment of a tyrosine phosphatase resulted in a 10.3 +/- 3.6-fold increase in channel activity with no change in the mean open time or amplitude. Orthovanadate had no effect on channel activity and, when added with the phosphatase, prevented the increase in activity. 4. Our results demonstrate that the basal activity of cation channels is increased by tyrosine dephosphorylation, suggesting a constitutive modulation of channel activity under resting conditions.